STRATEGI EFEKTIF MELIBATKAN KOMITE SEKOLAH DALAM MENINGKATKAN MUTU PENDIDIKAN DI SMP NEGERI 20 BANDAR LAMPUNG TAHUN PELAJARAN 2024/2025 - Effendi, Kurniawan (UNISAN JURNAL, 2025)
High-quality education is a cornerstone of sustainable community development. In this context, the School Committee’s role at SMP Negeri 20 Lampung becomes crucial in enhancing educational quality. This research aims to identify effective strategies that can be engaged by the School Committee and their impact on improving the school’s educational standards. Using a qualitative approach, data were collected from interviews, observations, and educational document analysis. The findings show that the involvement of the School Committee in curriculum planning, monitoring teaching and learning processes, and supporting educational facilities significantly contributes to improving educational quality. Therefore, this research encourages all educational stakeholders to actively involve the School Committee in strategic decision-making. Keywords: School Committee, educational quality, SMP Negeri 20, effective strategies, community roles.